Hasil validasi LKS berbasis problem solving untuk meningkatkan keterampilan berpikir kritis pada materi fluida statis dan fluida dinamis kelas XI SMA/MA - Dola Afriyenti; Yenni Darvina; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2019)
Education is an important parameter in the progress of a country. moving 21st century education empashasizes the ability of students to think critically, be able to connect sciense with the real word, master information technology to communicate and cellaborate. In the 21 st century human resource are needed which have competence.competence to form comparative, innovative, creative, competitive and collaborative human beings. Physics is a branch of science that has an important role in the development of science and technology, in physics subjects the ability to think logicaly, and systematically can be developed to equip students to be able to face challenges in a increasingly competitive society. The goverment has made various efforts to improve the quality of education. One of them is by applying problem based learning and requiring students to think critically. However, the real conditions at school show that the physics learning has not run well and the problem solving model is not yet fully implemented. One solution that can be used to overcome this problem solving based worksheet to improve critical thinking skills. The type of research is Research and Development (R & D). The object of this research is worksheets based problem solving on static fluid and dynamic fluid  class XI SMA/MA. The instrument for validating this learning material is a questionnaire sheet. The instrument for determining validity consists of six components, namely feasibility, model problem solving, critical thinking presentation, language, and graphics. Validator to obtain the validity of problem solving learning material consisting of 3 validators, namely physics lecturer FMIPA UNP. The data analysis technique is descriptive statistics. Based on data analysis, it can be concluded that the average value of the validation of physics teaching materials with problem solving on fluid static and dynamic fluid for the components of the six teaching materials is 90.51. Thus, the average value of the validation of physics teaching materials problem solving on static fluid and dynamic fluid can facilitate into very valid categories.